The Ti6Al4V Alloy Microstructure Modification Via Various Cooling Rates, its Influence on Hardness and Microhardness - Belan, Juraj; Uhricik, Milan; Hanusova, Patricia; Vasko, Alan (Manufacturing Technology Journal, 2020)
Titanium alloy Ti6Al4V falls into the group of alpha-beta titanium alloys and its widely used for engineering application due to its unique mechanical properties in regular or corrosion environments. Mechanical properties of alloy are strictly depending on final microstructure. The microstructure can be varying by various heat-treatment procedures. Heating slightly over beta-transus temperatures, 1050°C, with a dwell of 3 hours and cooling by various rates provide a wide possibility of microstructure modification. The cooling rates were represented by water quenching, air cooling, and furnace cooling. The microstructure has changed from the lamellar alpha-phase in prior beta-grains, through Widmanstatten microstructure to lamellar alpha prime-martensite structure due to cooling rates. After applied heat-treatment, the Vickers hardness HV10/10 (STN EN ISO 6507) and Vickers microhardness HV0.2/10 (STN EN ISO 6507) were done. The hardness and microhardness test results were compared to the starting stage. The Vickers hardness increases in all states about 8% for furnace cooling, 18% for air cooling, and almost 40% for water quenching. The same situation was for Vickers microhardness which increases about almost 29% for furnace cooling, 16% for air cooling, and 25% for water quenching. The hardness measurement shows increasing mechanical properties after all cooling rates. However, heat-treatment also shows negatives by creating the alpha-case layer and surface cracks, which is negative for the fatigue life of Ti6Al4V alloy.
Keywords: Ti6Al4V Alloy; beta-transus Annealing; Various Cooling Rates; Microstructure Modification; Vickers Hardness; Vickers Microhardness